Health-related quality of life and mental health of parents of children with pediatric abdominal tumors - Zierke, Kira; Boettcher, Michael; Behrendt, Paulina; Najem, Safiullah; Zapf, Holger; Reinshagen, Konrad; Wößmann, Wilhelm; Boettcher, Johannes (Children, 2024)
Background: Abdominal tumors rarely occur in childhood but are associated with great psychological stress for patients and their families. Parents playing a central role in their children’s treatment may experience adverse effects on their Health-Related Quality of Life (HRQoL) and mental health due to the children’s illness and required treatment. Given the limited knowledge of the psychosocial burden of parents with children suffering from solid abdominal tumors, this study aims to assess their HRQoL and mental health along with the impact of various psychosocial factors. Methods: A cross-sectional cohort study was carried out involving 54 parents of children with solid abdominal tumors who had surgery at the University Medical Center Hamburg-Eppendorf in Germany. The results were compared with 46 parents of children undergoing routine surgeries without a prior tumor diagnosis, and with normative values. Data were obtained using standardized questionnaires. Results: Parents of the index group showed significantly worse HRQoL and limited mental health. Furthermore, they showed significantly higher parental burden in several subscales and less social support in comparison with the control group. Conclusions: Considering the lower parental HRQoL and the central role parents play in their children’s lives, it is crucial to include prevention and intervention measures for parents as part of a multimodal treatment regime for children with solid pediatric abdominal tumors.
Gesehen am 10.03.2025